Nano Power Diplomacy Out Of the Mainstream - Purwasito, Andrik (Jurnal Mandala, 2018)
Nano power diplomacy is a diplomacy done by individuals and small groups, without bargaining and negotiating. Diplomacy without theoretical and scientific approaches, because it is just a small nod (actor unit) that does not carry a real-power set. Nano power diplomacy is an activity that emphasizes sharing of symbols between citizens, person to person direct contact. That is, nano power diplomacy is a diplomacy practice based on socio-cultural relations between people, between cultures, which tries to overcome differences and cultural barriers in building an equitable human community, such as race, ethnicity, customs, language, social level -economy, skin color and differences of trust and religion. A truly initiated diplomacy by the individual, which does not speak of conflict mediation and economic perspective, without bilateral, multilateral and summit meeting typologies, but diplomacy that emphasizes interpersonal communication and public communication. There is no secrecy, hidden agendas and transparencies, because every participant in nano power diplomacy is a human being who is born by a product of the same destiny, namely God the Creator. They multiply, eat and drink of the same type. They also have a lifestyle in much the same way. Finally, they also communicate in more or less the same way and pattern, verbal and non-verbal communication. Thus, human beings are universal beings who have the ability to live in kinship. Below is described the basic assumptions, methodology and notions of nano power diplomacy